2014
DOI: 10.5539/res.v6n1p61
|View full text |Cite
|
Sign up to set email alerts
|

Global Financial Crisis and Stock Market Integration between Northeast Asia and Europe

Abstract: This study examines the effect of financial crisis on the level of stock market integration. In particular, we investigated the dynamic movements of two regional stock markets, Northeast Asia and Europe during the period between January 1 st , 2000 and December 31 st , 2012, with particular attention placed on the global financial crisis (GFC). For this purpose, the paper employs various approaches including DCC-MGARCH, Risk Decomposition, GVAR, and CCOR models to ensure the robustness of empirical findings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
4
17
0
Order By: Relevance
“…Based on the estimates generated by the multivariate model, Figure was constructed to analyse the time varying nature of the correlations established between the five environmental segments. These results are consistent with those obtained in other research works on conventional indexes, namely, Li and Majerowska (), Dajcman et al () and Lee and Jeong (), in which the co‐movements between stock market returns are time varying.…”
Section: Data and Empirical Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the estimates generated by the multivariate model, Figure was constructed to analyse the time varying nature of the correlations established between the five environmental segments. These results are consistent with those obtained in other research works on conventional indexes, namely, Li and Majerowska (), Dajcman et al () and Lee and Jeong (), in which the co‐movements between stock market returns are time varying.…”
Section: Data and Empirical Analysissupporting
confidence: 92%
“…This highly asymmetric effect implies that each environmental segment reacts to different news sources from different segments and adjusts accordingly. This situation is quite similar to conventional markets, considering the results of other research studies, namely, those of Goeij and Marquering () and Lee and Jeong (). Additionally, the sum of the overall parameters of the model ( α + β < 1) is close to one, ensuring that the conditional correlation matrix is defined as positive, in accordance with the methodological proposals of Engle () and Tse and Tsui ().…”
Section: Data and Empirical Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…Since the variance decomposition requires estimates of infinite-horizontal expectations. The basic VAR methodology from Lee (2014) [10] is applied, but extended in various directions. Since VAR contributes a lot to the study of co-movements, this paper offers some of the theoretical introduction related to the VAR method.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical studies on the pre-crisis and crisis periods of the global financial crisis such as Lee and Jeong (2014) [10], have indicated that the level of market integration between Europe and other global stock markets had temporally increased during the global financial crisis. However, the level returned to its pre-crisis level in the post-crisis era.…”
Section: Research On Correlation Among Stock Marketmentioning
confidence: 99%